Design and optimization of the hydrokinetic turbine blades using statistical approaches - Kale, Fatih Mehmet; Yilmaz, Naz; Bademlioglu, Ali Husnu; Sokmen, Kemal Furkan; Shi, Weichao (Pergamon-Elsevier Science Ltd, 2026)
In this study, the design and optimization of Horizontal Axis Hydrokinetic Turbine (HAHT) blades were carried out using statistical approaches. Taguchi and ANOVA analyses were employed as the statistical methods. Initially, experimental and detailed computational analyses were conducted to predict the hydrodynamic performance of a HAHT. Subsequently, Taguchi and ANOVA analyses were performed to investigate the effects of design parameters such as thickness ratio (t/c), pitch angle (phi) and twist angle (theta) on the hydrodynamic performance of HAHT blades for different r/R blade sections 0.4, 0.6 and 0.8, and the optimal design parameters were identified. The study aims to investigate the effect of the design parameters, which are the most important in HAHT designs, on the power coefficient (CP) and to obtain the maximum CP for the existing HAHT as a result of changes proposed by the Taguchi and ANOVA optimization method. For the optimal HAHT geometry, the CP increase is observed between 2 % and 6 % at different TSR values. As a result of the analyses, the maximum CP was obtained as 0.4499 for the optimal design parameters. Additionally, it was concluded that the pitch angle was the most influential parameter on CP. Overall, the optimized blade provided a maximum 6 % increase in CP at TSR 5 compared to the initial design, and the pitch angle affected more than 96 % of this improvement compared to other parameters.
Keywords: Horizontal axis hydrokinetic turbine (HAHT); Computational fluid dynamics (CFD); Turbine blade design; Optimization; Taguchi method; ANOVA